Escolhas alimentares e composição nutricional de alimentos disponíveis em instituições de ensino pública e privada - Weber, Márcia Lopes [UNIFESP] (2009)
The aim of this study was: 1) to assess the nutritional quality of foods available to school children, comparing school meals prepared at public school to the nutritional quality of snacks sold at private school; and 2) to investigate the behavior of children´s food consumption in school. Sectional study was conducted in descriptive convenience sample of 7-10-y old schoolchildren of both genders (n=511), in one private school and one public school in Alfenas/MG, Brazil. The meals available in public school and the snacks sold in private schools were sampled daily for four weeks (a total of 45 samples) and analyzed for protein, fat, carbohydrate, energy, iron, salt and sodium. The results were compared to the nutritional standards for children aged 7-10 years. A questionnaire was used to obtain information of children´s food choice during stay in the school, about the type and frequency of food brought from home or purchased at school cafeteria. Weight and height data were taken to classify children´s nutritional status, and the prevalence of overweight was 24% in private school and 19% in public school. The children´s minimum nutritional recommendations were met in both schools. The concentration of protein, lipid, iron and sodium and the energy values of the foods at private schools were significantly higher than those of the public school. The range of macronutrients was more balanced in the meals in public schools, specially fat and protein. Snacks in private school were, in general, energy-dense. Intakes of salt were over twice the recommended amount, and for sodium the intakes were over three times, in both public and private schools. Overall, public school meals were of a better nutritional quality when compared to the private school snacks. The results showed that girls ate food from home in higher proportion in both schools, and food from cafeteria were consumed in similar proportions for all children, in both gender and schools. Significant differences were found in the consumption of salty snacks and candies in the public school when compared with private school. Milk and soft drinks were foods with lower and higher proportion of consumption, respectively, in both gender and school. Differences were observed in children´s food choices involving school type, gender and origin of food. These differences should be considered in developing strategies for nutrition counseling more effective in promoting sustainable changes in lifestyle. These strategies must involve parents, educators and children. In conclusion, corrective action is needed to adjust the wide variability in the energy and nutrient contents and in the sodium content of meals available in both public and private schools. The present study has demonstrated that foods with high energy content, sodium and or sugars and fat were consumed by children in higher proportion than healthier options, regarding of origin, gender, type of school. These findings suggest simultaneous and specific interventions strategies will be needed between family, school and government. These initiatives must have as its starting point the definition of public governmental policies at the federal level, which effectively normalize specific criteria for food sales in schools cafeteria, both public and private, and address monitoring and consequences for non-compliance to school principals.